Investigation on flavor and physicochemical properties of angel food cakes prepared by lactic acid fermented egg white. (15th July 2022) - Jia, Jie; Xiong, Dandan; Bai, Jie; Yuan, Yirong; Song, Qi; Lan, Tian; Tian, Liangjie; Guo, Chunfeng; Liu, Xuebo; Wang, Caixia; Duan, Xiang
Abstract: Our recent research revealed that moderate lactic acid fermentation endowed egg white with stronger foaming properties. This inspired us to further investigate the potential application of lactic acid fermented egg white in food system. In this paper, we systematically investigated the flavor and physicochemical properties of angel food cakes prepared by egg white fermented for different times (0, 3, 6 and 9 h). Results proved the utilization of 6 h-fermented egg white decreased the baking loss of cakes. And the flavor profiles of cakes with fermented egg white were significantly improved, resulting from the changed composition of egg white. The lightness, redness and yellowness were higher in cakes with 9 h-fermented egg white compared with control cakes. Meanwhile, the cakes with fermented egg white showed a lower volume and less resilient. These results suggested that fermented egg white could endow angel food cakes with improved aroma, and verified our previous viewpoint that lactic acid fermentation has a potential to be applied in egg products. Highlights: Cakes with fermented egg white exhibited improved flavor and color. Cake with fermented egg white exhibited lower baking loss. Cakes with 9 h-fermented egg white possessed the most pleasant aroma.